The Relationship between Repetitive Purchasing Intention and Ease of E-Commerce in Johor - Tan, Guan Xun; Hashim, Fazian (Research in Management of Technology and Business, 2025)
This study investigates the relationship between the ease of e-commerce and repetitive purchasing intentions among Generation Z consumers in Johor. Using a quantitative approach, data from 152 respondents were analyzed with SPSS. The findings reveal a significant positive correlation between perceived ease of use and repetitive purchasing intention, highlighting the importance of user-friendly interfaces, seamless navigation, and efficient purchasing processes in fostering customer loyalty. Trust and perceived usefulness were also identified as critical factors influencing consumer experiences and encouraging repeat purchases. High repetitive purchasing intention was linked to positive past interactions, platform familiarity, and intuitive e-commerce systems. These insights emphasize the need for secure, reliable, and personalized e-commerce platforms to influence consumer behavior and maintain a competitive edge. Businesses can enhance customer loyalty and retention by improving website usability, implementing robust security features, and offering tailored shopping experiences. This study contributes to the understanding of e-commerce consumer behavior and provides actionable strategies for online retailers to drive growth in a customer-centric digital marketplace.